Recent Research on Hybrid Hydrogels for Infection Treatment and Bone Repair - Mengjiao Cao; Chengcheng Liu; Mengxin Li; Xu Zhang; Li Peng; Lijia Liu; Jinfeng Liao; Jing Yang (Gels, 2022)
The repair of infected bone defects (IBDs) is still a great challenge in clinic. A successful treatment for IBDs should simultaneously resolve both infection control and bone defect repair. Hydrogels are water-swollen hydrophilic materials that maintain a distinct three-dimensional structure, helping load various antibacterial drugs and biomolecules. Hybrid hydrogels may potentially possess antibacterial ability and osteogenic activity. This review summarizes the recent progress of different kinds of antibacterial agents (including inorganic, organic, and natural) encapsulated in hydrogels. Several representative hydrogels of each category and their antibacterial mechanism and effect on bone repair are presented. Moreover, the advantages and disadvantages of antibacterial agent hybrid hydrogels are discussed. The challenge and future research directions are further prospected.